Definition of weakened zones from the standpoint of engineering geology and hydrogeology - А. S. Guseltsev (Известия высших учебных заведений: Геология и разведка, 2023)
Background. In recent decades, the concept of weakened zones has become widespread in various fields of Earth science. Thus, this concept is currently used in geology, mining, geomechanics, tectonics, geodynamics, and seismology. As a result, weakened zones can be considered and interpreted both as large fault zones, including dilatancy zones, and zones with sharply or quite noticeably changing physical and mechanical properties. At the same time, the purpose of studying and recording such zones also changes, depending on particular research tasks.Aim. To consider structures that are widely termed as weakened zones, although having received no clear definition and classification. To provide a definition of this term from the standpoint of hydrogeology and engineering geology.Materials and methods. The research basis was formed by the author’s long-term experience in the selection of sites for the location of nuclear energy facilities. The main methods included collection, generalization, and processing of information obtained by the author during fieldwork and laboratory research.Results. The author considers structures that are termed as weakened zones in Earth sciences, concerning a fairly wide range of structures and conditions of mountain ranges and soils. A definition of a weakened zone from the standpoint of hydrogeology and engineering geology is proposed. Various factors indicating the presence of weakened zones and possible negative consequences for engineering structures are considered.Conclusion. The concept of weakened zones should be taken into consideration when conducting detailed surveys of areas for the location of engineering facilities. It is noted that, when carrying out detailed surveys, the key to quantifying the characteristics of weakened zones in dispersed soils consists in a correct assessment of the spatial variability of soil parameters, largely the density of dry soil and porosity.